INNOVATIVE TECHNOLOGY OF SEED BREEDING OF ORIGINAL VARIETIES OF CUCURBITS CROPS - S. D. Sokolov; E. V. Khutornaya; A. S. Sokolov; A. M. Shantasov; Zh. R. Nugmanova (Овощи России, 2019)
A significant disadvantage of one-time seed fruit gatherings  used in operations  of seed farms is the usage of different-age  fruits (unripe, overripe and of optimally mature) for extracting seeds, that respectively have seeds with different sowing features. Carrying out several sequential  gatherings  that have not yet reached the biological maturity of the seed fruits, and their subsequent storage, makes it possible to avoid these problems. Through the example the Lunnyi watermelon  variety, the article presents the results of studying a new method of conducting seed production of polycarpous  varieties of cucurbits crops, including carrying out of frequent seed fruit gatherings  not in biological ripeness, but at the stage of technical maturity and subsequent storage of collected seed fruits seeds for some period until receiving by seeds of the high sowing  features. It has been established that for the production of certified seeds of the Lunnyi watermelon  variety, it is possible to collect 15-20-day-old fruits and store them for after-ripening purpose for 20  days before releasing  (extracting)  the seeds. The studied method allows to significantly  increase the overall productivity  of seed crops. Running the seed breeding of melons and gourds, which form a large number of fruits, based on frequent gatherings and subsequent storage of batches of seed fruits before seed extraction is very cost-effective and economically-viable, even despite a significant increase of the production cost by 30-40%. The method allows to increase the yield of seed material per area unit by 140-155% and to advance, first of all, the germination readiness of seeds to match the first class under the sowing features. On the basis of the conducted research, it was obtained a patent for the invention “Method of conducting seed production of polycarpous  varieties of vegetables and cucurbits crops”.